Experiencing Inoculation: A Qualitative Analysis of an Interrupted Message Design. Issue 1 (1st January 2023) - Parker, Kimberly A.; Hester, Erin B.; Ivanov, Bobi; Wombacher, Kevin; Watterson, Tara
Abstract : The persuasion literature shows robust support for the effectiveness of inoculation as a resistance strategy. Despite our more nuanced understanding of the theoretical process, scholars have yet to investigate how individuals experience inoculation as it occurs. Researchers conducted 31 in-depth interviews of men in a residential recovery facility. Interviews were collected at multiple points during the presentation of an inoculation message in order to collect participants' perceptions and responses to each message component. Deductive thematic analysis was used to determine how and why responses are elicited during inoculation, based on theoretical predictions. Findings illustrate that threat is experienced differently at multiple points throughout the inoculation message, suggesting that the forewarning and weakened counterarguments elicit unique expressions that resemble apprehension and motivation, respectively. Additionally, counterarguments stemming from the message content often take the form of direct refutations, focusing primarily on the long-term negative consequences of the threat (i.e., relapse).